Achievement of the sustainable development goals (SDG) in Portugal and forecast of key indicators until 2030 - Firoiu, Daniela; Ionescu, George H.; Pîrvu, Ramona; Bădîrcea, Roxana; Patrichi, Ioana C. (Technological and Economic Development of Economy, 2022)
In the current economic, social and political context, maintaining a stable trajectory of sustainable development, and thus achieving the UN Sustainable Development Goals, must be the central objective of every European country. The aim of this paper is to evaluate the level of achievement of the Sustainable Development Goals (SDGs) in Portugal, given that there were no similar published studies. The data used in the research was compiled from European Statistical Office – Eurostat, from 2007 until the most recent reports, and were processed and interpreted based on dynamic indices and time series forecasting (ARIMA model). Research results predict 57.50% achievement of the SDG targets, placing Portugal in the ranks of EU countries with high performance in terms of sustainable development and transition to a low-carbon economy.First published online 07 October 2022